Surgical volume-patient outcome relationships for parathyroidectomy in the England: analysis of an administrative dataset for the Getting It Right First Time programme. (1st March 2022) - Lansdown, Mark; Gray, William; Day, Jamie; Wass, John; Briggs, Tim
Abstract: Introduction: Previous studies suggest a relationship between surgical volume and patient outcomes for parathyroid surgery. However, most studies are small and from outside the UK. The aim of this study was to use Hospital Episodes Statistics to investigate volume-outcome relationships for parathyroid surgery in England. Methods: We examined a five-year period (April 2014-March 2019 inclusive) for elective, adult admissions for surgery for primary hyperparathyroidism without a diagnosis of multiple endocrine neoplasia, parathyroid cancer or renal disease. Volume was the number of procedures conducted in the same financial year as the index procedure. The primary outcome measure was emergency readmission at 30 days or length of stay greater than 2 days which were taken to represent poorer outcomes. Results: We included 17, 498 parathyroidectomies. Across the period the number of surgeons conducting parathyroid surgery changed little (280 in 2014/15 and 2018/19), although the number of procedures conducted rose from 3, 331 to 3, 848 per annum. From the lowest surgeon volume category (1–10 per annum) to the highest (≥ 60 per annum) the proportion of patients readmitted at 30 days or with an extended length of stay decreased 11.7% to 7.0%, diagnosis of hypoparathyroidism within one year from 16.3% to 10.9%, repeat parathyroid procedures within one year from 2.5% to 1.0% and mortality rate at one year from 1.0% to 0.5%. These differences persisted after adjustment for demographic and procedural covariates. Conclusion: Higher surgeon annual volume is associated with improved patient outcomes for parathyroid surgery. BAETS should consider recommending a minimum yearly workload.